2020
DOI: 10.1101/2020.04.03.023770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LCM-seq identifies robust markers of vulnerable and resistant human midbrain dopamine neurons

Abstract: Defining transcriptional profiles of substantia nigra pars compacta (SNc) and ventral tegmental area (VTA) dopamine neurons in human is critical to understanding their differential vulnerability in Parkinson Disease. However, reported marker profiles for these neuron populations are derived predominantly from rodents, utilize small sample sizes and display extensive variability between studies. Here, we map selective expression profiles of dopamine neurons in an extensive collection of human SNc and VTA using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The network was significantly enriched in terms related to collagen, extracellular matrix and basement membrane (FDR < 8.49 ´ 10 -4 ) (Figure 5A). Other studies have also implicated changes in the extracellular matrix as a result of PD (Aguila et al, 2021;Freitas et al, 2021;Sandor et al, 2017). One hub gene, Cacna1c, had 31 interactions (Figure 5B).…”
Section: Network Of Significant Differentially Expressed Genesmentioning
confidence: 83%
“…The network was significantly enriched in terms related to collagen, extracellular matrix and basement membrane (FDR < 8.49 ´ 10 -4 ) (Figure 5A). Other studies have also implicated changes in the extracellular matrix as a result of PD (Aguila et al, 2021;Freitas et al, 2021;Sandor et al, 2017). One hub gene, Cacna1c, had 31 interactions (Figure 5B).…”
Section: Network Of Significant Differentially Expressed Genesmentioning
confidence: 83%
“…Our findings may also be relevant for the understanding of human disease. A recent study into the transcriptomes of human midbrain DA neurons found that KCNIP4 expression is a key molecular signature of VTA DA neurons (as opposed to SN DA neurons) and is also strongly associated with DA neuron survival in Parkinson's disease (Aguila et al, 2021). While this study did not differentiate between different KCNIP4 isoforms, it could be that the differential expression of KChIP4a plays an important role in determining DA neuron vulnerability in Parkinson's disease, especially since Kv4 current reductions in SN DA neurons have been observed in experimental models of this illness (Subramaniam et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our estimation is approximate to the fold-change (134-fold) of Rpl22 HA immunoprecipitation (IP) in ipsilateral motoneurons compared to the contralateral ones from RiboTag; ChAT Cre mouse model at 7 days post-SNC (Shadrach et al, 2021), suggesting high reproducibility and accuracy of our data. Besides, we employed bootstrapping strategy to identify robust differential expression genes (DEGs) (Aguila et al, 2021) and showed remarkably robust (R90%) differential expression of Atf3 in state 2 and state 3 (Figure S5). The SCENIC (Aibar et al, 2017) analysis showed that the activity of Atf3 regulon was also significantly higher in state 2 and state 3, indicating Atf3 was mostly activated as early as 1 day (Student's t test, *p < 0.05, **p < 0.0001, Figure S5).…”
Section: Two Distinct Clusters Were Revealed By Lcm-seqmentioning
confidence: 99%
“…Moreover, captured and discriminated ''intact'' motoneurons and its minimal niches at 1, 3, and 7 days provide a valuable control for further screening crucial molecules involved in axon regeneration. We next employed bootstrap strategy (Aguila et al, 2021) to identify robust and reliable DEGs (average frequency R50%). 80 robust DEGs presented in early injury (61 up-and 19 downregulated genes, 0.5-12 h, Figure 3B and Table S3).…”
Section: Robustly Differentially Expressed Genes Of Mn Niches In Resp...mentioning
confidence: 99%
See 1 more Smart Citation